(untitled) (Analysis in Theory and Applications, 2022)
The aim of this paper is to define (p, q)-analogue of Mittag-Leffler Function, by using (p, q)-Gamma function. Some transformation formulae are also derived by using the (p, q)-derivative. The (p, q)-analogue for this function provides elegant generalization of q-analogue of Mittag-Leffler function in connection with q-calculus. Moreover, the (p, q)-Laplace Transform of the Mittag-Leffler function has been obtained. Some special cases have also been discussed.